Costs of Loyalty Programmes Implementation in Pharmacies - Maria Sierpińska; Agnieszka Woś (Contemporary Economics)
Receiving the customer is in today’s market realities top marketing companies. The build a sustainable partnership relation between the seller and the buyer is decide on businesses, takings and profit potential. Increasingly, therefore, perpetuates the view that create lasting relationships is an essential factor in improving the effectiveness of marketing activities conducted by modern businesses. The paper presents the implementation costs of loyalty programmes in pharmacies. These costs are presented based on a study of one of the largest pharmacy loyalty programmes in Poland: “I care for health”.